Retrospective study of the frequency of diagnosing diffuse changes in the liver parenchyma according to the results of radiological studies - N.Yu. Ziuz; V.M. Bogomaz (Gastroenterologìa)
Background. The prevalence of chronic liver pathology is high and increasing in most countries of the world. Objective: to evaluate the incidence rate of structural diffuse changes in the liver using radiological methods in different sex-age groups of the adult population. Materials and methods. 65,570 unique protocols of ultrasound examination and 1,212 magnetic resonance imaging (MRI) of the hepatobiliary system were studied in patients aged 18 years and older. During the statistical analysis of quantitative features, the distribution of indicators for normality was checked according to the Shapiro-Wilk test. The chi-square test was used to compare frequencies. To determine the relationship between the risk of diffuse liver changes and factor characteristics, we used the method of building logistic regression models. To assess the relationship between the factor traits and the resulting trait, the odds ratio (OR) and 95% confidence interval (CI) were calculated. To assess the quality of the model’s prediction, the area under the curve (AUC) and 95% CI were calculated. The level of statistical significance was chosen at 5 % (p = 0.05). The study was approved by the local ethics committee. Results. The frequency of diagnosing diffuse changes in the liver parenchyma during B-mode ultrasound examination in the total sample was 12.5 % (in women — 8.7 %, in men — 18.2 %). A statistically significant increase (p < 0.01) in the risk of developing diffuse changes in the liver was found (OR = 1.01 (95% CI 1.01–1.02 %) with increasing age for each year. In the univariate logistic regression model, men had a 2.3 times higher chances of developing diffuse liver changes than women (p < 0.01), AUC = 0.604 (95% CI 0.598–0.61 %). In the general sample of patients who underwent MRI of the hepatobiliary system, the frequency of diagnosing fatty infiltration of the liver was 37 % (95% CI 34.3–39.8 %). In particular, among 700 women, the frequency of incidents was 34.1 % (95% CI 30.7–37.7 %), among 512 men — 41.0 % (95% CI 36.8–45.3 %). Conclusions. The prevalence of diffuse liver changes is high (12.5 % according to ultrasound and 37 % according to MRI) and increases with age among the adult population of working age. Given the variety of factors contributing to the progression of chronic liver diseases and the importance of identifying patients at high risk of developing liver cirrhosis, there is a need for widespread implementation of non-invasive diagnostic tests and technical upgrading of specialized healthcare facilities. The data obtained can serve as landmarks for calculating the needs for secondary care and improving clinical pathways for patients.